2021
DOI: 10.1177/0954406221993844
|View full text |Cite
|
Sign up to set email alerts
|

Machinability investigation and sustainability assessment in hard turning of AISI D3 steel with coated carbide tool under nanofluid minimum quantity lubrication-cooling condition

Abstract: The present research addresses the machinability of hardened die steel (AISI D3, 61HRC) in hard turning using multilayer (TiCN/Al2O3/TiN) coated carbide tool under nanofluid based minimum quantity lubrication-cooling condition, where no previous data are available. Power consumption, flank wear, chip morphology and surface integrity (microhardness, residual stress, white layer formation, machined surface morphology, and surface roughness) are considered as technological performance characteristics to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…29 Considering these reports, researchers are giving more emphasis to reduce the electricity consumption in several machining activities. 30…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Considering these reports, researchers are giving more emphasis to reduce the electricity consumption in several machining activities. 30…”
Section: Resultsmentioning
confidence: 99%
“…29 Considering these reports, researchers are giving more emphasis to reduce the electricity consumption in several machining activities. 30 The present research estimated the power consumption in the CBN tool-assisted hard turning. The measured power consumption for L 27 experiments was displayed in Table 1.…”
Section: Analysis Of Power Consumptionmentioning
confidence: 98%
“…One unit of electricity (≈1 kWh) emits 0.523 kg of CO 2 as per Ministry of Energy in India. 53,54 It is observed that machining under MQL at optimal parametric conditions reduces energy consumption (53.96%) and enhances carbon footprints savings (68.46 kg of CO 2 ) and thus saves in manufacturing cost Thus environmentally conscious MQL machining provides better economical and socio-technological benefits towards green machining and cleaner production for industry as per sustainability concern.…”
Section: Sustainability Assessmentmentioning
confidence: 99%
“…However, none of these studies explored in a systematic way, which is required for worthwhile research in terms of uniqueness to consider the physical aspect of machining science. From the open literature, it is clear that many investigators have carried out Al 2 O 3 -based ceramic tools during machining to assess their cutting performance [ 31 , 32 , 33 ]. However, the use of newer generation silicon-strengthened.…”
Section: Introductionmentioning
confidence: 99%